Adjunctive intraocular and peri-ocular steroid (triamcinolone acetonide) versus standard treatment in eyes undergoing vitreoretinal surgery for open globe trauma (ASCOT): study protocol for a phase III, multi-centre, double-masked randomised controlled trial. Issue 1 (December 2016) - Banerjee, Philip; Cornelius, Victoria; Phillips, Rachel; Lo, Jessica; Bunce, Catey; Kelly, Joanna; Murphy, Caroline; Edwards, Rhiannon; Robertson, Elizabeth; Charteris, David
Abstract Background Eyes sustaining open globe trauma are at high risk of severe visual impairment. Ocular injuries which result in visual loss invariably affect the posterior segment of the eye, and prevention of visual loss involves posterior segment (vitreoretinal) surgery. Despite improvements in vitreoretinal surgical techniques, outcomes in these patients remain unsatisfactory, and development of the intraocular scarring response proliferative vitreoretinopathy is the leading cause. Proliferative vitreoretinopathy is the most common cause of recurrent retinal detachment in these eyes; it is reported to occur in up to 45 % of cases. Methods/design The Adjunctive Steroid Combination in Ocular Trauma (ASCOT) trial is a multi-centre, double-masked, parallel-arm randomised controlled trial with an internal pilot designed to investigate the effectiveness and cost-effectiveness of using intravitreal and sub-Tenon's triamcinolone acetonide peri-operatively in patients undergoing vitrectomy following open globe trauma. In total, 300 eyes of 300 patients will be recruited and randomly allocated to one of two treatment groups. Both groups will receive standard surgical treatment and routine pre-operative and post-operative treatment and care. The treatment group will receive an adjunctive peri-operative steroid combination (triamcinolone acetonide) consisting of 4 mg/0.1 ml into the vitreous cavity and 40 mg/1 ml into the sub-Tenon's space. The trial incorporates a two-stage internal pilot to examine projected recruitment and retention rates. Progression criteria from the internal pilot study will enable us to determine whether to undertake the main trial. Patients and primary outcome assessors will be masked to treatment allocation. The primary outcome will be an improvement from baseline to 6 months of at least 10 on the corrected visual acuity as measured by ETDRS letter score. Secondary outcomes will be development of scarring, retinal detachment, intraocular pressure abnormalities, quality of life and public sector service use. Discussion This is the first powered, controlled clinical trial to investigate the use of adjunctive triamcinolone in patients undergoing vitrectomy following open globe trauma. Trial registration EudraCT2014-002193-37 . Registered on 5 September 2014. ISRCTN30012492 . Registered on 5 September 2014.